Antibabylonische Polemik im priesterlichen Schöpfungsbericht? - Gertz, Jan Christian (Zeitschrift für Theologie und Kirche, 2009)
An examination of the suggestion of anti-Babylonian polemics in the priestly creation account - as it is often claimed - shows that there is no evidence for an anti-Babylonian orientation in Genesis 1. This is especially the case in regard to the creation of the heavenly bodies (Gen 1:14-19). Instead we have to consider that Genesis 1 was part of an Eastern Mediterranean koiné, i.e. a culture area in which during the 7th century BCE a new form of natural science established itself that received its main impulses from Mesopotamia.
Keywords: Bibel -- Genesis; Bibel -- Genesis -- 1; Bibel -- Genesis -- 1,14-19; Priesterschrift; Religion; Mesopotamien; Kultur; Babylonisch; Schöpfungsglaube; Babylonien; Bibel / Genesis